P102 A survey of home oxygen provision across London. (2nd December 2011) - Davidson, A C; Williams, S; Baxter, N; Morris, E; Restrick, L
Abstract : Introduction: In preparing for 2012, we undertook a survey of current oxygen provision across London. Methods: A questionnaire was sent electronically (Survey Monkey) to 100 BTS Oxygen champions, oxygen leads in primary and secondary care, PCT prescribing advisors and community respiratory nurses around London. Results: From 60 returns the main findings were: 75% of LTOT prescriptions initiated by hospitals yet no follow-up in 35%. 70% community teams reported "not at all" and "only sometimes" being informed about new starters by GPs and hospitals. <50% took action when concordance reports showed variance (under or over use) from prescribed treatment. Lack of ability to detect hypoxic patients with >20% community healthcare sites not having access to an oximeter. Fire safety officers are rarely advised about the persistent smoker (only 16%) despite the potential risk to patients, their families and the general public. Local guidance on appropriate steps to take is rare (35%). 3 HOS units denied LTOT for smokers and one assessed this by exhaled carbon monoxide measurement. A variety of methods for protecting patients from excessive oxygen are favoured but use appears limited. When asked what policy respondents favoured, universal precaution (as promoted by ambulance guidelines) was most popular (60%) while 20% favoured oxygen cards and 20% patient specific protocols (PSP). A specific local policy for removing oxygen when no longer indicated or used is rare (<25%). This, coupled with inadequate follow-up of patients started on oxygen during hospital admission, suggests significant waste with the current oxygen provision. Respondents indicated guidance on oxygen removal, contract monitoring, assessment for ambulatory oxygen and training in arterial or capillary blood gases as being required. Conclusions: Problems in healthcare coordination, public and patient safety and in removing oxygen once ordered were common. There is a need to integrate hospital and community teams and to prepare for safe mobilisation and contract management so that a quality home oxygen service can be provided in the future.